Defending our rainforest: A gude to community based ecoturism in the Ecuadorian Amazon / Rolf Wesche y Andy Drumm - Wesche, Rolf. Drumm, Andy (Ecuador : Abya Yala, 1999)
Trata sobre el activismo ambiental y la protección de la selva amazónica.
1. The geographical context 2. The role of the responsible traveler
incluye índice
Col. Agro
Keywords: 1. COMMUNITY BASED ECOTURISM 2. TIPS FOR TRAVELER